War and law in the Islamic world - Vanhullebusch, Matthias (Brill's Arab and Islamic laws series, 2015)
Principles of protection in warfare under Islamic law of war -- Principles of protection in warfare under international humanitarian law -- The "western" self and the other -- The "Islamic" self and the other -- The structure of the legal arguments in Islamic law of war -- The structure of the legal arguments in international humanitarian law